PATROLI MERUPAKAN PENCEGAHAN DAN PENINDAKAN - Candra, Addy (Universitas Prof. Dr. Hazairin, SH, 2020)
This study aims to determine the background of Patrol and Prevention and Enforcement, Authority in carrying out the tasks ordered, Patrol officers or the Patrol team have the authority as regulated in the applicable law. The method used in this paper is a normative-empirical approach. Whereas the patrol leader must monitor the conduct of the patrol by its members, if the patrol member misuses his / her authority, which leads to an illegal act, the patrol officer can be brought to court.